المستوي التركيبي في الدعاء القرآني - بور، رائدة علي Bour, Raedah Ali; غانمى، محمد جواد إسماعيل (جامعة الكوفة - كلية الآداب, 2018)
Quranic pray method is distanced by art statement and firm style and strong and unparalleled tissue. this is essay is invest gating stylish compound level in Quranic pray. and has an important role in showing the structural elements of Quranic pray. the conclusion of this discussion shows that consists of compound dimension in Quranic pray like originative and predicative. noun and verb clauses are used there alternately that is suitable for the kinds of pray then it shows kinds of formulas that are used in Quranic pray like imperative and negative interrogation. choosing they styles and imperative sentences is not random but is has the most care lessness and influence on the reader and harmony is seen clearly between the sentences and their meaning.
يتميز الدعاء القرآني بتعبيره الفني وأسلوبه الجزل وصياغته المحكمة. استهدف هذا المقال دراسة أسلوبية للمستوى التركيبي في الدعاء القرآني الذي يلعب دوراً هاما ف بنيوية الدعاء ومكوناته التركيبية مستخدما المنهج الوصفي التحليلي وتشير نتائج البحث إلى أن السمات التركيبية في الدعاء تتجلي في استخدام الجمل الإنشائية والخبرية وتوظيف الجمل الإسمية والفعلية وصلتها بنوع الدعاء وتنوع صيغه كالأمر والنهي والاستفهام. واختيار الألفاظ والجمل لم يكن أمراً تصادفياً بل أنها تميزت بالدقة وقوة التأثير في المتلقي وأن التناسق الفني قد ظهر بين الجمل ومعانيها بصورة واضحة.
Keywords: القرآن الكريم -- الأدعية القرآنية -- البلاغة العربية -- التراكيب اللغوية -- الجمل الانشائية